(1392) feasibility appraisal of Damietta port project a case study on financial profitability analysis-a case study on financial profitability analysis دراسة جدوى مشروع ميناء دمياط: دراسة حالة حول تحليل الربحية المالية - farahat, A. M. (The Institute Of National Planning., 2018)
As a result of the congestion-problem in.the Egyptian ports and the identified need for additional port capacities, the Ministry of Development and New Communities on behalf of the Egyptian Government, has requested in April 1977 the services of a foreign consultant* to carry out a master plan for the establish me' of‘a new port_facility at Damietta.